Muzyczna złożoność i pewna specyficzna forma doświadczenia estetycznego - Moraczewski, Krzysztof (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
The main topic of the article is the explanation of repeatable interpretationsof the experience of music in terms of the experience of eternity. The problem is approachedby introducing Kant's concept of the mathematical/dynamic sublime and then by suggesting that the experience of the mathematical sublime can be also achived on a waywhich Kant did not analyze, i.e. thanks to the contact with aesthetical complexity. Theconditions of such an experience are being researched. The second point of delibarationconcerns the transition from experiencing the complex as sublime to interpreting it assymbol of the eternal. The examples used are coming mainly from the field of music,including J.S. Bach and O. Messiaen.